Knowledge, attitude and practice of diabetic foot care in patients in HUMS polyclinic, Sabah - Shaila Kabir; ABM Tofazzal Hossain; Rosnah Majin; Sabrina Paul; Hamidah Hassan (Malaysian Journal of Medicine and Health Sciences, 2020)
Diabetic foot is an alarming complication of Diabetes Mellitus, results from neurological and vascular insufficiencies. If untreated, it may lead to amputation, resulting in a significant reduction in the quality of life and increase the risk of early death. Proper foot care with daily foot inspection and hygiene can prevent amputations. The objective of this study is to evaluate the knowledge, attitude, and practise of Diabetic foot care thus to establish the baseline reference for the effective foot care education and to propose an intervention method that is suitable for various cultural, religious and local circumstances. Methods: It was a cross-sectional survey conducted on diabetic patients who are seeking health care at HUMS Polyclinic, Kota Kinabalu, Sabah. A semi-structured Knowledge, Attitude and Practice validated questionnaire were used to get the information. Results: Around 93% of 30 diabetic patients knew that the self-examination was required but only 14 patients (46%)had the proper knowledge of foot care. Only 50% of respondent knew the correct way of cutting nails. 53% of the respondents were aware of prop¬er foot-ware. The attitudes towards diabetic foot care, 96% were motivated to perform self-care. Although a high percentage of patients knew about diabetic foot care, but in practice the activities such as washing (100%), proper drying (83%), moisturizing (90%) and massaging (46%) were not executed together. Regarding nail cutting, only 33% practices proper technique and only 40% uses proper foot ware. Conclusions: Early detection and recognition of high-risk feet by patients and health care providers at regular intervals should be encouraged. It is essential to improve the awareness and practice of diabetic foot care daily by patients. Effective educational strategies should be established for both the health care providers and diabetic patients to create awareness for effective foot care.